Way out there: pathogens, health, and condition of overwintering salmon in the Gulf of Alaska - Christoph M. Deeg; Albina N. Kanzeparova; Alexei A. Somov; Svetlana Esenkulova; Emiliano Di Cicco; Karia H. Kaukinen; Amy Tabata; Tobi J. Ming; Shaorong Li; Gideon Mordecai; Angela Schulze; Kristina M. Miller (Canadian Science Publishing, 2022)
Salmon are keystone species across the North Pacific, supporting ecosystems, commercial opportunities, and cultural identity. Nevertheless, many wild salmon stocks have experienced significant declines. Salmon restoration efforts focus on fresh and coastal waters, but little is known about the open ocean environment. Here we use high throughput RT-qPCR tools to provide the first report on the health, condition, and infection profile of coho, chum, pink, and sockeye salmon in the Gulf of Alaska during the 2019 winter. We found lower infectious agent number, diversity, and burden compared with coastal British Columbia in all species except coho, which exhibited elevated stock-specific infection profiles. We identified Loma sp. and Ichthyophonus hoferi as key pathogens, suggesting transmission in the open ocean. Reduced prey availability, potentially linked to change in ocean conditions due to an El Niño event, correlated with energetic deficits and immunosuppression in salmon. Immunosuppressed individuals showed higher relative infection burden and higher prevalence of opportunistic pathogens. We highlight the cumulative effects of infection and environmental stressors on overwintering salmon, establishing a baseline to document the impacts of a changing ocean on salmon.